Winning From Failing - Seibert, Josh (Ascent Audio, 2020)
In the real world, adults don't learn by memorizing facts. There's a natural learning progression from acquiring knowledge to the application in the work role, to developing skills, to adopting new, productive habits. It looks like this: Knowledge > Application > Skills > Habits > Results = Learning Inevitably, there are failures along the way. These failures are part of the learning process . . . but too often, our learning initiatives, and our working cultures, make failure taboo. No one wants to be seen failing. Josh Seibert's new book Winning From Failing: Build And Lead A Corporate Learning Culture For High Performance shows company leaders how to harness the natural adult learning progression. His book shows sales leaders (and others) how to create, support, and sustain a workplace learning culture that measurably improves performance. Launching such a culture always starts with top management's recognition that it is it okay, even essential, for people to fail . . . within clearly defined boundaries. Winning From Failing is a proven roadmap for creating a high-performance learning culture in the workplace, based on the principles of the Sandler Selling System.
Online resource; Title from title page (viewed December 29, 2020)
Keywords: Audiobooks; Livres audio